The service quality dimension and level of satisfaction among patients attending 1 malaysia clinic in Kota Bharu, Kelantan - Zun , Ahmad Badruridzwanullah (2017)
In Malaysia, 60% of public primary care services comprise of Public Health Clinic,Maternal and Child Health Clinic and Rural Health Clinic are located at rural area (Family Health Development Division, 2016). This is because, previously population in Malaysia were concentrated in rural area. However, for past 10 years, urbanization occurred drastically in Malaysia which leads to migration of people from rural area to the urban area. This subsequently can lead to health inequity caused by maldistribution of health service. Urbanization caused reshaping population health problems, particularly among the urban poor, towards non-communicable diseases, accidental and violent injuries, and deaths and impact from ecological disaster (Campbell and Campbell, 2007).In order to overcome this issue, 1 Malaysia Clinic was first introduced on 23 October 2009 during National Budget 2010 presentation by Prime Minister Dato’ Sri Mohd Najib Tun Abd Razak adaptation from 1 Malaysia Concept “People First, Performance Now”. The objective of 1 Malaysia Clinic is to facilitate and extend the access of healthcare services to all nations especially among low income population in urban area.